Long-term economic evaluation of the recombinant Mycobacterium tuberculosis fusion protein (EC) test for the diagnosis of Mycobacterium tuberculosis infection - Sha Diao; Sha Diao; Sha Diao; Sha Diao; Zheng Liu; Zheng Liu; Zheng Liu; Zheng Liu; Zheng Liu; Dan Liu; Dan Liu; Dan Liu; et al. (Frontiers Media S.A., 2023)
Background: Tuberculosis continues to be a significant global burden. Purified protein derivative of tuberculin (TB-PPD) is one type of tuberculin skin test (TST) and is used commonly for the auxiliary diagnosis of tuberculosis. The recombinant Mycobacterium tuberculosis fusion protein (EC) test is a new test developed in China.Objective: Evaluate the long-term economic implications of using the EC test compared with the TB-PPD test to provide a reference for clinical decision-making.Methods: The target population was people at a high risk persons of being infected with Mycobacterium tuberculosis. The outcome indicator was quality-adjusted life years (QALY). A cost-utility analysis was used to evaluate the long-term economic implications of using the EC test compared with the TB-PPD test. We employed a decision tree-Markov model from the perspective of the whole society within 77 years.Results: Compared with the TB-PPD test, the EC test had a lower cost but higher QALY. The incremental cost-utility ratio was −119,800.7381 CNY/QALY. That is, for each additional QALY, the EC test could save 119,800.7381 CNY: the EC test was more economical than the TB-PPD test.Conclusion: Compared with the TB-PPD test, the EC test would be more economical in the long term for the diagnosis of M. tuberculosis infection according our study.